The “Biological Weapons” of Ehrlichia chaffeensis: Novel Molecules and Mechanisms to Subjugate Host Cells - Rikihisa, Yasuko (Frontiers in Cellular and Infection Microbiology, 2022)
Ehrlichia chaffeensis is an obligatory intracellular bacterium that causes human monocytic ehrlichiosis, an emerging, potentially fatal tick-borne infectious disease. The bacterium enters human cells via the binding of its unique outer-membrane invasin EtpE to the cognate receptor DNase X on the host-cell plasma membrane; this triggers actin polymerization and filopodia formation at the site of E. chaffeensis binding, and blocks activation of phagocyte NADPH oxidase that catalyzes the generation of microbicidal reactive oxygen species. Subsequently, the bacterium replicates by hijacking/dysregulating host-cell functions using Type IV secretion effectors. For example, the Ehrlichia translocated factor (Etf)-1 enters mitochondria and inhibits mitochondria-mediated apoptosis of host cells. Etf-1 also induces autophagy mediated by the small GTPase RAB5, the result being the liberation of catabolites for proliferation inside host cells. Moreover, Etf-2 competes with the RAB5 GTPase-activating protein, for binding to RAB5-GTP on the surface of E. chaffeensis inclusions, which blocks GTP hydrolysis and consequently prevents the fusion of inclusions with host-cell lysosomes. Etf-3 binds ferritin light chain to induce ferritinophagy to obtain intracellular iron. To enable E. chaffeensis to rapidly adapt to the host environment and proliferate, the bacterium must acquire host membrane cholesterol and glycerophospholipids for the purpose of producing large amounts of its own membrane. Future studies on the arsenal of unique Ehrlichia molecules and their interplay with host-cell components will undoubtedly advance our understanding of the molecular mechanisms of obligatory intracellular infection and may identify hitherto unrecognized signaling pathways of human hosts. Such data could be exploited for development of treatment and control measures for ehrlichiosis as well as other ailments that potentially could involve the same host-cell signaling pathways that are appropriated by E. chaffeensis.